Transplantation of human bone marrow‐derived clonal mesenchymal stem cells reduces fibrotic scar formation in a rat spinal cord injury model. (9th June 2017) - Kim, Moonhang; Kim, Kil Hwan; Song, Sun U; Yi, Tac Ghee; Yoon, Seung Hwan; Park, So Ra; Choi, Byung Hyune
Abstract: This study aimed to evaluate the therapeutic effect on tissue repair and scar formation of human bone marrow‐derived clonal mesenchymal stem cells (hcMSCs) homogeneously isolated by using a subfractionation culturing method, in comparison with the non‐clonal MSCs (hMSCs), in a rat spinal cord injury (SCI) model. The SCI was made using a vascular clip at the T9 level. Cells were transplanted into the lesion site 3 days after injury. A functional test was performed over 4 weeks employing a BBB score. Rats were killed for histological analysis at 3 days, 1 week and 4 weeks after injury. The transplantation of hMSCs and hcMSCs significantly reduced lesion size and the fluid‐filled cavity at 4 weeks in comparison with the control group injected with phosphate buffered saline (PBS) ( p < 0.01). Transplantation of hcMSCs showed more axons reserved than that of hMSCs in the lesion epicentre filled with non‐neuronal tissues. In addition, hMSCs and hcMSCs clearly reduced the inflammatory reaction and intraparenchymal hemorrhaging, compared with the PBS group. Interestingly, hcMSCs largely decreased Col IV expression, one of the markers of fibrotic scars. hcMSCs yielded therapeutic effects more than equal to those of hMSCs on the SCI. Both hMSCs and hcMSCs created an increase in axon regeneration and reduced scar formation around the SCI lesion. Copyright © 2017 John Wiley & Sons, Ltd.